MATERNAL MORTALITY (1962-1986) - Ludmir C., Abraham (2015)
We report on maternal mortality experience in almost 25 years of obstetrical activity in the former Maternity Hospital of St. Bartholomew; center dedicated since the beginning of the reconstruction (in 1961), teaching at undergraduate and graduate and care of their community. It was the first hospital where the residentado of Obstetrics and Gynecology was established in the Republic, with a philosophy and preventive technology, girded with stiffness current nomenclature and suggestions of institutions of higher. It is a State entity, with 79 obstetric beds and around 4,400 births a year, which goes a population of low-to medium low and has managed to maintain a maternal mortality rate of 527/10000 births nv In recent years, a figure, below that observed in other nosocomial, with the same characteristics in the country. Which shows that it is feasible to reduce deaths from obstetric causes, if awareness of the problem becomes and technical attitudes especially in particular are kept in educational institutions that should be governing in a country like ours, in development .